(untitled) (Tanzania Medical Journal, 2021)
Background Peptic ulcer is one of gastrointestinal (GI) disease presenting with dyspeptic symptoms whose cause often overlaps making the etiological diagnosis difficult. Endoscopy remains to be the ideal for identifying organic disease of foregut. Helicobacter pylori (H. pylori) infection has commonly been associated with most and various upper gastrointestinal pathologies. Broad Objective This scholarly cross-sectional study was conducted to determine the association between H. pylori infection and peptic ulcer disease in 116 dyspeptic patients who visited Gastroentorology Unit at Muhimbili National Hospital in Dar es Salaam located in the eastern coast of Tanzania. The study aimed at obtaining data that could be used as bench mark for future H. pylori screening as a preventive measure to control peptic ulcer disease (PUD) in Tanzania. Methods The study included all patients with dyspeptic symptoms visiting and/or referred to Gastroenterology Unit from 1st to 30th August 2015. Dyspepsia was defined as persistent or recurrent pain or discomfort in the upper abdomen. Patients diagnosed with PUD within the observation period were verified through medical records. Information on psychosocial factors, medication and symptoms was obtained from a questionnaire completed at study entry. In this study H. pylori infection status was determined serologically. Results The most commonly identified endoscopic findings were gastritis which accounted for 44 (37.9%) patients, gastro esophageal disease accounting for 35 (30.2%) patients and peptic ulcer disease in 30 (25.9%) patients. Among patients with peptic ulcer disease, 17 (56.7%) had H. pylori infections. The association between peptic ulcer disease and H. pylori infection was statistically significant (p-value < 0.001). Neither gastritis nor GERD was found to be associated with H. pylori infection. Conclusion There is a statistically significant association between H. pylori and PUD (gastric and duodenal ulcers), a signature to previous reports out of our settings. Our study benchmarks the need for further studies focusing on screening, for early diagnosis and predictions to establish the existing relationships and possible cofounders in these proposed relationships. The increasing number of reported PUD at MNH and presence of H. pylori infection warrant studies targeting to investigate the co-existence of these two closely linked GIT conditions. Key words: Peptic Ulcer Disease, GI ulcer types, H. pylori, screening.